Polysaccharide niche partitioning of distinct Polaribacter clades during North Sea spring algal blooms - Avcı, Burak; Krüger, Karen; Fuchs, Bernhard M.; Teeling, Hanno; Amann, Rudolf I. (The ISME Journal, 2020)
Massive releases of organic substrates during marine algal blooms trigger growth of many clades of heterotrophic bacteria. Algal polysaccharides represent the most diverse and structurally complex class of these substrates, yet their role in shaping the microbial community composition is poorly understood. We investigated, whether polysaccharide utilization capabilities contribute to niche differentiation of Polaribacter spp. (class Flavobacteriia ; known to include relevant polysaccharide-degraders) that were abundant during 2009–2012 spring algal blooms in the southern North Sea. We identified six distinct Polaribacter clades using phylogenetic and phylogenomic analyses, quantified their abundances via fluorescence in situ hybridization, compared metagenome-assembled genomes, and assessed in situ gene expression using metaproteomics. Four clades with distinct polysaccharide niches were dominating. Polaribacter 2-a comprised typical first responders featuring small genomes with limited polysaccharide utilization capacities. Polaribacter 3-a were abundant only in 2010 and possessed a distinct sulfated α-glucoronomannan degradation potential. Polaribacter 3-b responded late in blooms and had the capacity to utilize sulfated xylan. Polaribacter 1-a featured high numbers of glycan degradation genes and were particularly abundant following Chattonella algae blooms. These results support the hypothesis that sympatric Polaribacter clades occupy distinct glycan niches during North Sea spring algal blooms.